Clinical profile of Female Urinary Incontinence: A Hospital Based Study - Shrestha, Alka (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To determine the prevalence of urinary incontinence of women attending gynae outdoor patient department. Method: It is a prospective cross sectional study conducted at Paropakar Maternity and Women’s Hospital for three months. Types of incontinence, their presentation, associated factors, age and parity were the variables studied. Data were analyzed by descriptive statistics. Results: Out of 950 gynaecological out-patients, 97 had urinary incontinence(10.2%); 34.1% were in 50- 59 years and 37.2% were multipara. Stressurinary incontinence (SUI) was the most common incontinence (56.7%) followed by mixed urinary incontinence (22.7%) and urge urinary incontinence (20.6%). Common complaints were leakage during coughing (63.6%) and sneezing(18.2%) in SUI;urgency and frequency were main problem in mixed and urge urinary incontinence. Three-fourth cases had associated medical conditions and rest had gynecological factors. Conclusions: Urinary incontinence is common in the fifth decade of life of women and more than half had stress incontinence.